NUSANTARA MASK HERITAGE MALAYSIA: INFOGRAPHIC APPLICATION DEVELOPMENT OF MASKS OF MALAYSIAN INDIGENOUS TRIBES AT THE MUSEUM OF ASIAN ART MALAYSIA BASED ON AUGMENTED REALITY AS MEDIA OF TOURISM EDUCATION - Lisa Sidyawati; Joni Agung Sudarmanto; Abdul Rahman Prasetyo; Encik Muhammad Hawari Bin Berahim (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2019)
The museum is a fun learning tool for the community. The Museum of Asian Art is one of the museums in Malaysia which was founded by Malaya University. The museum has three showroom floors and represents three civilizations; India, China and Islam. Every day the museum is very crowded by tourists to find information about artifact objects. Lots of artifacts stored in this museum include textiles, musical instruments, ceramics, masks, paintings, weapons and others. The museum itself is the right place to store and preserve ancient objects so they can still be seen and used as a source of learning and cultural preservation for the nation's next generation. This research takes the artifacts that are masks because the results of observations made by researchers, information about masks at the Museum of Asian Art Malaysia is very minimal compared to other artifacts, there are only name tags but there is no deeper information about the mask. So that it still cannot be used as a learning medium to the maximum. From this problem, researchers developed Nusantara Mask Heritage Malaysia (NUSMARI MALAYSIA) products based on Augmented Reality. The research method used is the development model into 4 steps: (1). Research and Information Collecting, (2). Planning, (3). Develop Preliminary Form Of Product, (4). Final Product Revision. The result of this development is a learning media application that can help tourists of all ages to more easily learn the mask of the Orang Asli Malaysia in the museum.